MGO3 and GIP1 act synergistically for the maintenance of centromeric cohesion. (2nd January 2017) - Batzenschlager, Morgane; Schmit, Anne-Catherine; Herzog, Etienne; Fuchs, Joerg; Schubert, Veit; Houlné, Guy; Chabouté, Marie-Edith
ABSTRACT: The control of genomic maintenance during S phase is crucial in eukaryotes. It involves the establishment of sister chromatid cohesion, ensuring faithful chromosome segregation, as well as proper DNA replication and repair to preserve genetic information. In animals, nuclear periphery proteins - including inner nuclear membrane proteins and nuclear pore-associated components - are key factors which regulate DNA integrity. Corresponding functional homologues are not so well known in plants which may have developed specific mechanisms due to their sessile life. We have already characterized the Gamma-tubulin Complex Protein 3-interacting proteins (GIPs) as essential regulators of centromeric cohesion at the nuclear periphery. GIPs were also shown to interact with TSA1, first described as a partner of the epigenetic regulator MGOUN3 (MGO3)/BRUSHY1 (BRU1)/TONSOKU (TSK) involved in genomic maintenance. Here, using genetic analyses, we show that the mgo3gip1 mutants display an impaired and pleiotropic development including fasciation. We also provide evidence for the contribution of both MGO3 and GIP1 to the regulation of centromeric cohesion in Arabidopsis.